Modelling Variable Speed Pumps for Flow and Pressure Control Using Nash Equilibrium - Jochen W. Deuerlein; Sylvan Elhay; Olivier Piller; Michael Fischer; Angus R. Simpson (Engineering Proceedings)
Recently, the Nash equilibrium, known from game theory, was used for steady state calculation of pressurized pipe systems with general flow and pressure control devices. The concept is now applied to pumping stations. It is assumed that at least one of the pumps has a frequency controller that enables the pump to deliver a given set flow or set pressure by adaptation of pump speed. For hydraulic calculation, the system is decomposed into the local pumping station and a surrogate link with flow or pressure constraints at one of its end nodes. This method is demonstrated for a small example system.